Analisis Penyusunan dan Implementasi Anggaran Neraca pada PT Indofood Sukses Makmur Tbk - Helvi Viola Sari; Muhammad Syahwildan (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the preparation and implementation of the balance sheet budget at PT Indofood Sukses Makmur Tbk, a multinational company engaged in the food and agribusiness sector. The balance sheet budget is a projection of the company’s financial position, including assets, liabilities, and equity at the end of a specific period, which plays a crucial role in supporting strategic decision-making. The research method used is descriptive qualitative with a literature study approach and analysis of the interim consolidated financial statements as of December 31, 2024, and March 31, 2025. The results show that the company's total assets increased by IDR 7.53 trillion (3.7%) in the first quarter of 2025, mainly due to significant increases in cash and cash equivalents as well as trade receivables. The company’s liabilities also rose by IDR 3.94 trillion, largely stemming from an increase in short-term bank loans and tax payables. Equity also grew through the accumulation of retained earnings and an increase in non-controlling interests. These findings highlight the importance of accurate balance sheet budgeting in optimizing financial planning and performance control. This research contributes to managerial understanding in formulating financial strategies based on balance sheet projections.